2015
DOI: 10.15611/pn.2015.379.41
|View full text |Cite
|
Sign up to set email alerts
|

Problemy asymetrii informacji na rynku turystycznym w obszarze transakcyjnym

Abstract: Informacje o naborze artykułów i zasadach recenzowania znajdują się na stronie internetowej Wydawnictwa www.pracenaukowe.ue.wroc.pl www.wydawnictwo.ue.wroc.pl Publikacja udostępniona na licencji Creative Commons Uznanie autorstwa-Użycie niekomercyjne-Bez utworów zależnych 3.0 Polska (CC BY-NC-ND 3.0 PL)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 2 publications
0
8
0
1
Order By: Relevance
“…In addition, when other functional forms were tested, the results showed that the linear function produces the best outcomes. This type of function is expressed as Equation (1). Following this formula, the subsequent Xs An analysis was carried out of the relative number of beds for each city in March 2019.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, when other functional forms were tested, the results showed that the linear function produces the best outcomes. This type of function is expressed as Equation (1). Following this formula, the subsequent Xs An analysis was carried out of the relative number of beds for each city in March 2019.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the issues of sustainable tourism (Panasiuk 2021a), including overtourism, and social issues, such as tourism-phobia, are also important. The functioning of the tourism market is also influenced by new ix technologies, artificial intelligence, robotization (Panasiuk 2015), and thus the creation of alternative ways to spend free time. These subject areas can therefore be addressed in the next issue of the Economies Special Issue.…”
Section: Preface To "Tourism Economics"mentioning
confidence: 99%
See 2 more Smart Citations
“…Wielkość sprzedaży jest bardzo silnie uzależniona od pozycjonowania oferty, która to jest również przedmiotem sprzedaży przez OTA. Asymetria siły przetargowej pomiędzy pośrednikiem a dostawcą usług cząstkowych jest jednak znacznie większa, gdyż linie lotnicze z natury są znacznie większymi przedsiębiorstwami niż przedsiębiorstwa hotelarskie (Panasiuk, 2015).…”
Section: Problemy Relacji Między Ota I Przedsiębiorstwami Hotelarskimiunclassified